A composite steel core high manganese high strength steel welding rod and preparation method thereof
The composite steel core high manganese high-strength steel welding rod addresses 'tail red' issues by stabilizing the arc and preventing coating failure, improving welding efficiency and reducing waste through a specific composition and structure.
Patent Information
- Application Number
- CN202411305884.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
High manganese steel welding rods for LNG storage tanks suffer from 'tail red' issues, where the welding rod heats up and cracks, leading to poor welding performance and waste due to frequent rod replacement.
A composite steel core high manganese high-strength steel welding rod is developed, comprising a powder core wrapped in a steel strip with a coating, containing specific alloying elements and additives to stabilize the arc and reduce thermal expansion, thereby preventing coating cracking and improving welding efficiency.
The composite welding rod maintains stable arcs, reduces spatter, and prevents coating failure, enhancing welding efficiency and reducing waste by allowing continuous welding without rod replacement.
Smart Images

Figure CN118808994B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding materials, and particularly relates to a composite steel core high manganese high strength steel welding rod and a preparation method thereof. Background Art
[0002] In recent years, with the increasing attention paid to environmental protection and energy in the world, the demand for liquefied natural gas (LNG) in various countries has continued to increase. Most traditional LNG storage tanks are built with high manganese steel with good performance and low price. High manganese steel is an alloy steel containing a high proportion of manganese (usually more than 10%), and its tensile strength is generally between 600~900MPa, which belongs to the category of high-strength steel (tensile strength ≥550Mpa). At present, in the high manganese steel supporting welding rods for LNG storage tanks, the steel core is austenitic high manganese steel core, but the high manganese steel core has a large linear expansion coefficient, poor thermal conductivity, and high resistivity. It generates heat seriously during welding, causing the welding rod to heat up and turn red at about 1 / 2~1 / 3 of the rear end, and the coating cracks and falls off at high temperature (commonly known as "tail red"), which deteriorates the welding process performance, is prone to welding defects, and ultimately affects the weld performance. In order to avoid welding defects, many welders stop welding when the welding rod begins to turn red and replace new welding rods, which causes great waste. Summary of the invention
[0003] In view of the above shortcomings of the prior art, the present invention provides a composite steel core high manganese high strength steel welding rod and a preparation method thereof, which effectively alleviates the red tail problem of the existing high manganese high strength steel welding rod, can greatly improve welding efficiency and reduce waste, and has great practical significance for promotion.
[0004] To achieve the above-mentioned purpose and other related purposes, the present invention provides a composite steel core high manganese high-strength steel welding rod, comprising a powder core, a steel strip and a coating, wherein the powder core is wrapped inside the steel strip, and the coating is coated outside the steel strip. Based on 100 parts by weight of the powder core, the powder core comprises the following components and the weight proportions of each component are respectively: 50-62 parts of electrolytic manganese powder; 5-10 parts of chromium powder; 5-8 parts of nickel powder; 0.8-1.5 parts of copper powder; 1.5-3 parts of 45# ferrosilicon; 3-6 parts of ferrochromium nitride; 1.5-3 parts of ferroboron; 0.5-1.5 parts of lithium fluoride; 0.8-1.2 parts of graphite; the remainder is reduced iron powder and unavoidable impurities.
[0005] In one example of the present invention, the steel strip is a low-carbon steel strip, and the steel strip includes the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05%, S≤0.02%, P≤0.02%, and the rest is Fe and unavoidable impurities.
[0006] In one example of the present invention, the coating includes the following components and the weight proportions of each component are: 40-50 parts of marble, 3-6 parts of strontium carbonate, 25-30 parts of fluorite, 6-10 parts of rutile, 3-5 parts of phlogopite, 2-4 parts of silica powder, 2-4 parts of alumina, 0.1-1 parts of carboxymethyl cellulose (CMC), and 0.1-1 parts of potassium alginate.
[0007] In an example of the present invention, the weight of the powder core is 22-27% of the total weight of the welding rod; the weight of the steel strip is 28-38% of the total weight of the welding rod; and the weight of the coating is 40-45% of the total weight of the welding rod.
[0008] The present invention also provides a method for preparing a composite steel core high manganese high strength steel welding rod, comprising the following steps:
[0009] The components of the powder core are sieved separately and weighed according to the ratio, and mixed evenly to obtain a powder core mixed powder;
[0010] Wrapping the powder core mixed powder in a steel strip to obtain a seamless composite steel core;
[0011] The components of the coating are sieved respectively and weighed and mixed according to a ratio to obtain a coating powder, and a binder is added to the coating powder and stirred evenly to obtain a coating mixture;
[0012] The coating mixture is press-coated on the surface of the seamless composite steel core, and after drying, a composite steel core high-manganese high-strength steel welding rod is obtained.
[0013] In one example of the present invention, electrolytic manganese powder, chromium powder, nickel powder, copper powder, 45# ferrosilicon, ferrochromium nitride, ferroboron, reduced iron powder, lithium fluoride and alumina are sieved through a 60-mesh sieve, marble, strontium carbonate, fluorite, rutile and phlogopite are sieved through a 40-mesh sieve, and silicon micropowder is sieved through a 120-mesh sieve.
[0014] In one example of the present invention, wrapping the powder core mixed powder in the steel strip to obtain a seamless composite steel core includes the following steps:
[0015] Rolling the steel strip into a U-shaped groove;
[0016] Filling the powder core mixed powder into the U-shaped groove;
[0017] The U-shaped groove containing the powder core mixed powder is closed, rolled into an O-shape, welded, and drawn to a set diameter.
[0018] In an example of the present invention, the diameter of the seamless composite steel core is 2.5-5 mm.
[0019] In one example of the present invention, the amount of the binder added is 19-21% of the total weight of the coating powder, and the binder is a water glass binder with a potassium-sodium weight ratio of 1:1.
[0020] In an example of the present invention, the drying temperature is 300-350° C., and the drying time is 120-150 min.
[0021] The composite steel core high manganese high-strength steel welding rod of the present application has a powder core wrapped inside a steel strip to form a composite steel core, and a coating is wrapped outside the composite steel core. Since the inside of the composite steel core is not solid, even when the temperature rise of the steel core is large during ultra-large current welding, the external expansion of the steel core is much smaller than the internal expansion, and no large pressure is exerted on the external coating. Therefore, there is no problem of coating cracking or falling off, and efficient welding can be achieved to reduce waste. Furthermore, lithium fluoride with excellent arc stabilization performance is added to the powder core as an arc stabilizer. Since the powder core is wrapped in a steel strip, the moisture absorption of lithium fluoride can be effectively alleviated. Therefore, the arc is more stable and the spatter is smaller during welding, which is more conducive to the welder to control the molten pool and obtain high-quality welds. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 It is a schematic structural diagram of a composite steel core high manganese high strength steel welding rod in one embodiment of the present invention;
[0024] Figure 2 It is a preparation flow chart of the composite steel core high manganese high strength steel welding rod of the present invention in one embodiment;
[0025] Figure 3 FIG. 4 is a preparation flow chart of step S2 in one embodiment.
[0026] Component number description
[0027] 100, powder core; 200, steel strip; 300, coating. DETAILED DESCRIPTION
[0028] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0029] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0030] It should be noted that “%” and “wt%” in this specification represent mass percentage, and “part” represents part by weight.
[0031] See also Figure 1 The present invention provides a composite steel core high manganese high strength steel electrode, which comprises a powder core 100, a steel strip 200 and a coating 300, wherein the powder core 100 is wrapped inside the steel strip 200, and the coating 300 is coated outside the steel strip 200. Taking the weight of the powder core 100 as 100 parts, the powder core 100 comprises the following components and the weight of each component is respectively: 50-62 parts of electrolytic manganese powder; 5-10 parts of chromium powder; 5-8 parts of nickel powder; 0.8-1.5 parts of copper powder; 1.5-3 parts of 45# ferrosilicon; 3-6 parts of ferrochrome nitride; 1.5-3 parts of ferroboron; 0.5-1.5 parts of lithium fluoride; 0.8-1.2 parts of graphite; the remainder is reduced iron powder and unavoidable impurities.
[0032] In one embodiment, the coating 300 includes the following components and the weight proportions of each component are: 40-50 parts of marble, 3-6 parts of strontium carbonate, 25-30 parts of fluorite, 6-10 parts of rutile, 3-5 parts of phlogopite, 2-4 parts of silica powder, 2-4 parts of aluminum oxide, 0.1-1 parts of carboxymethyl cellulose, and 0.1-1 parts of potassium alginate.
[0033] In the present application, the functions of the components in the powder core 100 and the coating 300 are as follows:
[0034] Electrolytic manganese powder: The most important alloying element, Mn element transitions to the weld, and works together with C, Ni, and N to keep the weld austenite at room temperature, while reducing O and S impurity elements in the weld. Too much addition will reduce the crack resistance and toughness of the weld, while too little addition will result in insufficient weld strength.
[0035] Chromium powder: alloying element, transfer Cr element to weld, improve weld strength. Too much addition will produce chromium carbide between grains, deteriorate toughness, too little addition will lead to insufficient weld strength.
[0036] Nickel powder: An expensive alloying element, it transfers Ni elements into the weld to improve the low-temperature impact toughness of the weld. Adding too much will result in high costs, while adding too little will result in insufficient low-temperature toughness.
[0037] Copper powder: Adding a small amount of Cu element to the weld can effectively inhibit the formation of martensite phase and help improve the plasticity of the weld.
[0038] 45# Ferrosilicon: Mainly used as a deoxidizer and alloying agent. Adding too much will increase spatter and reduce toughness, while adding too little will lead to poor molten pool fluidity and poor weld mechanical properties.
[0039] Ferrochromium nitride: A small amount of N element is transferred to the weld to stabilize the austenite structure and improve the strength of the weld. Too much addition will produce a large amount of nitrides and reduce the toughness of the weld.
[0040] Ferroboron: A small amount of B element can reduce the viscosity of the molten pool and improve the spread of the weld.
[0041] Graphite: On the one hand, it transitions to the austenitizing element C in the weld to maintain good mechanical properties; on the other hand, it is used as a lubricant to improve the fluidity of the internal powder core and avoid component segregation.
[0042] Reduced iron powder: added as a surplus, mainly used to improve the arc state and adjust the fluidity of molten iron.
[0043] Marble and strontium carbonate: Both powders are carbonates, which are the main gasifiers and slag-forming agents. They improve the viscosity of the slag and promote the fineness of the weld. Strontium carbonate can effectively improve the crack resistance of the coating. Too much carbonate is not conducive to the formation of the weld, and too little carbonate will lead to problems such as pores and incomplete slag coverage.
[0044] Fluorite: The main component is CaF2, which has the functions of slag formation, deoxidation and dehydrogenation. It can adjust the viscosity of slag and improve the fluidity of weld. The F element combines with the harmful element H to reduce the H content in the weld and purify the weld. Too much addition will lead to poor weld formation, and too little addition will easily cause porosity defects.
[0045] Rutile, silica powder, and alumina: All three are acidic oxides, and their main functions are slag formation, adjusting slag alkalinity, reducing splashing, and improving slag viscosity. Adding too much will cause a sharp increase in viscosity and large splashing, while adding too little will not have an obvious effect.
[0046] Phlogopite and lithium fluoride: the main arc stabilizers. The low-ionized substances they contain, such as K, Li and other elements, can effectively increase the stability of the arc. Lithium fluoride has excellent arc stabilization and dehydrogenation capabilities. If too much is added, the cost of the electrode will be too high and the amount of smoke will increase. If too little is added, the arc stabilization effect will not be obvious.
[0047] Carboxymethyl cellulose, sodium alginate: can improve the coating performance of welding rods.
[0048] In one embodiment, the steel strip 200 is a low-carbon steel strip, including the following components and the weight percentage of each component: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05%, S≤0.02%, P≤0.02%, and the rest is Fe and inevitable impurities. The resistivity of the low-carbon steel strip is only 1 / 4~1 / 5 of that of austenitic steel, and the temperature rise during welding is small and the linear expansion phenomenon is not obvious.
[0049] In one embodiment, the weight of the powder core 100 is 22-27% of the total weight of the welding rod; the weight of the steel strip 200 is 28-38% of the total weight of the welding rod; and the weight of the coating 300 is 40-45% of the total weight of the welding rod.
[0050] The composite steel core high manganese and high-strength steel welding rod of the present application can effectively alleviate the tail red problem of the existing high manganese and high-strength steel welding rod, and there is no problem of cracking and falling off of the coating at the rear end of welding. The welding arc is stable, spatter is small, slag is easy to remove, and the anti-pore ability is strong. It can greatly improve welding efficiency and reduce waste, and has great practical significance for promotion.
[0051] See also Figure 2 The present invention also provides a method for preparing a composite steel core high manganese high strength steel welding rod, comprising the following steps:
[0052] S1. Sieve the components of the powder core separately, weigh them according to the ratio, and mix them evenly to obtain a powder core mixed powder;
[0053] S2, wrapping the powder core mixed powder in a steel strip to obtain a seamless composite steel core;
[0054] S3, sieving the components of the coating respectively and weighing and mixing them according to the ratio to obtain coating powder, adding a binder to the coating powder and stirring evenly to obtain a coating mixture;
[0055] S4. Press-coat the coating mixture on the surface of the seamless composite steel core, and obtain the composite steel core high manganese high-strength steel welding rod after drying.
[0056] In step S1, the powder core includes the following components, and the weight proportions of each component are respectively: 50-62 parts of electrolytic manganese powder; 5-10 parts of chromium powder; 5-8 parts of nickel powder; 0.8-1.5 parts of copper powder; 1.5-3 parts of 45# ferrosilicon; 3-6 parts of ferrochrome nitride; 1.5-3 parts of ferroboron; 0.5-1.5 parts of lithium fluoride; 0.8-1.2 parts of graphite; the remainder is reduced iron powder and unavoidable impurities. Exemplarily, electrolytic manganese powder, chromium powder, nickel powder, copper powder, 45# ferrosilicon, ferrochrome nitride, ferroboron, reduced iron powder, lithium fluoride and alumina are sieved through a 60-mesh sieve.
[0057] In step S2, the seamless composite steel core has a better moisture-proof effect, which can effectively prevent lithium fluoride from absorbing moisture, making the arc more stable and spatter smaller during welding, and making it easier for welders to control the molten pool and obtain high-quality welds.
[0058] See also Figure 3 In one embodiment, a seamless composite steel core is prepared by referring to the manufacturing process of a seamless flux-cored welding wire, comprising the following steps:
[0059] S21, rolling the steel strip into a U-shaped groove;
[0060] S22, filling the powder core mixed powder into the U-shaped groove;
[0061] S22, closing the U-shaped groove containing the powder core mixed powder, rolling it into an O-shape, welding it, and drawing it to a set diameter.
[0062] In this embodiment, the steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05%, S≤0.02%, P≤0.02%, and the rest is Fe and unavoidable impurities.
[0063] In one embodiment, the diameter of the seamless composite steel core is 2.5-5 mm, for example, 2.5 mm, 3 mm, 4 mm, 4.5 mm or 5 mm.
[0064] In step S3, the coating includes the following components and the weight proportions of each component are: 40-50 parts of marble, 3-6 parts of strontium carbonate, 25-30 parts of fluorite, 6-10 parts of rutile, 3-5 parts of phlogopite, 2-4 parts of silica powder, 2-4 parts of alumina, 0.1-1 parts of carboxymethyl cellulose, and 0.1-1 parts of potassium alginate. Exemplarily, marble, strontium carbonate, fluorite, rutile and phlogopite are sieved through a 40-mesh sieve, and silica powder is sieved through a 120-mesh sieve.
[0065] In one embodiment, the amount of binder added is 19-21% of the total weight of the coating powder, such as 19%, 20% or 21%. Exemplarily, the binder is a water glass binder with a potassium-sodium weight ratio of 1:1.
[0066] In step S4, the drying temperature is 300-350°C, for example, 300°C, 320°C, 340°C or 350°C; the drying time is 120-150 min, for example, 120 min, 130 min, 140 min or 150 min.
[0067] In the present application, the powder core stirring and the coating stirring are both carried out using conventional stirring devices and conventional stirring methods in the art, and the pressure coating is carried out using conventional pressure coating devices and conventional pressure coating methods in the art, which will not be described in detail here.
[0068] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0069] In the following examples, electrolytic manganese powder, chromium powder, nickel powder, copper powder, 45# ferrosilicon, ferrochromium nitride, ferroboron, reduced iron powder, lithium fluoride, and alumina were sieved through a 60-mesh sieve, marble, strontium carbonate, fluorite, rutile, and phlogopite were sieved through a 40-mesh sieve, and silicon micropowder was sieved through a 120-mesh sieve.
[0070] Example 1
[0071] The high manganese high-strength steel electrode of this embodiment includes a powder core, a steel strip and a coating, the powder core is wrapped inside the steel strip, and the coating is coated on the outside of the steel strip. Taking the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 60 parts of electrolytic manganese powder, 6 parts of chromium powder, 7 parts of nickel powder, 1 part of copper powder, 1.8 parts of 45# ferrosilicon, 3.8 parts of ferrochrome nitride, 2.2 parts of ferroboron, 0.8 parts of lithium fluoride, 1.1 parts of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05, S≤0.02, P≤0.02, and the balance is Fe and unavoidable impurities. The coating comprises the following components and the weight proportions of the components are: 43 parts of marble, 5.5 parts of strontium carbonate, 28 parts of fluorite, 7 parts of rutile, 4 parts of phlogopite, 2.5 parts of silica powder, 3.5 parts of aluminum oxide, 0.6 parts of CMC and 0.6 parts of potassium alginate.
[0072] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain a powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with the powder core mixed powder, the U-shaped groove containing the powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to 2.5mm to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain a coating powder, and a water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed onto the surface of the composite steel core, and dried at 300°C for 150 minutes to obtain a composite steel core high manganese high-strength steel welding rod. In this embodiment, the weight of the powder core is 26% of the total weight of the welding rod, the weight of the steel strip is 33% of the total weight of the welding rod, the weight of the coating is 41% of the total weight of the welding rod, and the amount of binder added is 21% of the total weight of the coating powder.
[0073] Example 2
[0074] The high manganese high-strength steel electrode of this embodiment includes a powder core, a steel strip and a coating, the powder core is wrapped inside the steel strip, and the coating is coated on the outside of the steel strip. Taking the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 55 parts of electrolytic manganese powder, 8.5 parts of chromium powder, 5.8 parts of nickel powder, 1.3 parts of copper powder, 1.6 parts of 45# ferrosilicon, 4.5 parts of ferrochromium nitride, 1.8 parts of ferroboron, 1.2 parts of lithium fluoride, 0.8 parts of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C: ≤0.04%, Mn: 0.10%~0.25%, Si: ≤0.05, S: ≤0.02, P: ≤0.02, and the balance is Fe and unavoidable impurities. The coating comprises the following components and the weight proportions of the components are: 45 parts of marble, 5.6 parts of strontium carbonate, 25.5 parts of fluorite, 9 parts of rutile, 3.5 parts of phlogopite, 3.2 parts of silica powder, 2 parts of alumina, 0.8 parts of CMC and 0.8 parts of potassium alginate.
[0075] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with powder core mixed powder, the U-shaped groove containing powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to 5mm to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain coating powder, and water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed onto the surface of the composite steel core, and dried at 330°C for 120 minutes to obtain a composite steel core high manganese high-strength steel electrode. In this embodiment, the weight of the powder core is 25% of the total weight of the electrode, the weight of the steel strip is 31% of the total weight of the electrode, the weight of the coating is 44% of the total weight of the electrode, and the amount of binder added is 20% of the total weight of the coating powder.
[0076] Example 3
[0077] The high manganese high-strength steel electrode of this embodiment includes a powder core, a steel strip and a coating, the powder core is wrapped inside the steel strip, and the coating is coated on the outside of the steel strip. Taking the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 52 parts of electrolytic manganese powder, 9.2 parts of chromium powder, 6.6 parts of nickel powder, 1.4 parts of copper powder, 2.8 parts of 45# ferrosilicon, 3.8 parts of ferrochrome nitride, 2.6 parts of ferroboron, 0.7 parts of lithium fluoride, 0.9 parts of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05, S≤0.02, P≤0.02, and the balance is Fe and unavoidable impurities. The coating includes the following components and the weight proportions of each component are: 47 parts of marble, 3.6 parts of strontium carbonate, 29 parts of fluorite, 7.5 parts of rutile, 4.5 parts of phlogopite, 3.1 parts of silica powder, 2.8 parts of alumina, 0.9 parts of CMC, 0.3 parts of potassium alginate, and the amount of binder added is 19% of the total weight of the coating powder.
[0078] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain a powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with the powder core mixed powder, the U-shaped groove containing the powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to 3.2 mm to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain a coating powder, and a water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed onto the surface of the composite steel core, and a composite steel core high manganese high-strength steel electrode is obtained after drying at 310°C for 150 minutes. In this embodiment, the weight of the powder core is 23% of the total weight of the electrode, the weight of the steel strip is 35% of the total weight of the electrode, the weight of the coating is 42% of the total weight of the electrode, and the amount of binder added is 19% of the total weight of the coating powder.
[0079] Example 4
[0080] The high manganese high-strength steel electrode of this embodiment includes a powder core, a steel strip and a coating, the powder core is wrapped inside the steel strip, and the coating is coated on the outside of the steel strip. Taking the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 56 parts of electrolytic manganese powder, 6.8 parts of chromium powder, 7.2 parts of nickel powder, 1.1 parts of copper powder, 2.6 parts of 45# ferrosilicon, 5.6 parts of ferrochromium nitride, 2.1 parts of ferroboron, 1.1 parts of lithium fluoride, 0.8 parts of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05, S≤0.02, P≤0.02, and the balance is Fe and unavoidable impurities. The coating includes the following components and the weight proportions of the components are: 49 parts of marble, 5.2 parts of strontium carbonate, 27.2 parts of fluorite, 6.5 parts of rutile, 3.2 parts of phlogopite, 3.8 parts of silica powder, 3.2 parts of alumina, 0.9 parts of CMC and 0.3 parts of potassium alginate.
[0081] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with powder core mixed powder, the U-shaped groove containing powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to 4mm to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain coating powder, and water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed onto the surface of the composite steel core, and dried at 350°C for 130 minutes to obtain a composite steel core high manganese high-strength steel electrode. In this embodiment, the weight of the powder core is 23% of the total weight of the electrode, the weight of the steel strip is 36% of the total weight of the electrode, the weight of the coating is 41% of the total weight of the electrode, and the amount of binder added is 19% of the total weight of the coating powder.
[0082] Example 5
[0083] The high manganese high-strength steel electrode of this embodiment includes a powder core, a steel strip and a coating, the powder core is wrapped inside the steel strip, and the coating is coated on the outside of the steel strip. Taking the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 62 parts of electrolytic manganese powder, 5 parts of chromium powder, 5 parts of nickel powder, 1.5 parts of copper powder, 3 parts of 45# ferrosilicon, 6 parts of ferrochromium nitride, 1.5 parts of ferroboron, 1.5 parts of lithium fluoride, 1.2 parts of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05, S≤0.02, P≤0.02, and the balance is Fe and unavoidable impurities. The coating comprises the following components and the weight proportions of the components are: 40 parts of marble, 6 parts of strontium carbonate, 25 parts of fluorite, 6 parts of rutile, 3 parts of phlogopite, 4 parts of silica powder, 4 parts of alumina, 0.1 parts of CMC and 1 part of potassium alginate.
[0084] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain a powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with the powder core mixed powder, the U-shaped groove containing the powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to 3mm to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain a coating powder, and a water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed onto the surface of the composite steel core, and dried at 330°C for 140 minutes to obtain a composite steel core high manganese high-strength steel welding rod. In this embodiment, the weight of the powder core is 22% of the total weight of the welding rod, the weight of the steel strip is 38% of the total weight of the welding rod, the weight of the coating is 40% of the total weight of the welding rod, and the amount of binder added is 21% of the total weight of the coating powder.
[0085] Example 6
[0086] The high manganese high-strength steel electrode of this embodiment includes a powder core, a steel strip and a coating, the powder core is wrapped inside the steel strip, and the coating is coated on the outside of the steel strip. Taking the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 50 parts of electrolytic manganese powder, 10 parts of chromium powder, 8 parts of nickel powder, 0.8 parts of copper powder, 1.5 parts of 45# ferrosilicon, 3 parts of ferrochromium nitride, 3 parts of ferroboron, 0.5 parts of lithium fluoride, 1 part of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05, S≤0.02, P≤0.02, and the balance is Fe and unavoidable impurities. The coating comprises the following components and the weight proportions of the components are: 50 parts of marble, 3 parts of strontium carbonate, 30 parts of fluorite, 10 parts of rutile, 5 parts of phlogopite, 2 parts of silica powder, 2 parts of alumina, 1 part of CMC and 0.1 part of potassium alginate.
[0087] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with powder core mixed powder, the U-shaped groove containing powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to 4.5mm to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain coating powder, and water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed on the surface of the composite steel core, and dried at 320°C for 140 minutes to obtain a composite steel core high manganese high-strength steel electrode. In this embodiment, the weight of the powder core is 27% of the total weight of the electrode, the weight of the steel strip is 28% of the total weight of the electrode, the weight of the coating is 45% of the total weight of the electrode, and the amount of binder added is 20.5% of the total weight of the coating powder.
[0088] Comparative Example 1
[0089] The welding rod of this comparative example includes a powder core, a steel strip and a coating, wherein the powder core is wrapped inside the steel strip and the coating is coated outside the steel strip. Based on the weight of the powder core as 100 parts, the powder core includes the following components and the weight of each component is: 56 parts of electrolytic manganese powder, 6.8 parts of chromium powder, 7.2 parts of nickel powder, 1.1 parts of copper powder, 2.6 parts of 45# ferrosilicon, 5.6 parts of ferrochrome nitride, 2.1 parts of ferroboron, 0.2 parts of lithium fluoride, 0.8 parts of graphite, and the balance is reduced iron powder and unavoidable impurities. The steel strip is a low-carbon steel strip, including the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%-0.25%, Si≤0.05, S≤0.02, P≤0.02, and the balance is Fe and unavoidable impurities. The coating includes the following components and the weight proportions of the components are: 35 parts of marble, 5.8 parts of strontium carbonate, 27.2 parts of fluorite, 7.2 parts of rutile, 3.2 parts of phlogopite, 3.8 parts of silica powder, 3.2 parts of alumina, 0.9 parts of CMC and 0.3 parts of potassium alginate.
[0090] The groups of powder cores are sieved separately and weighed according to the above ratio, and mixed evenly to obtain powder core mixed powder; the steel strip is rolled into a U-shaped groove and filled with powder core mixed powder, the U-shaped groove containing powder core mixed powder is closed, rolled into an O-shaped and welded, and drawn to a set diameter to obtain a composite steel core. The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain coating powder, and water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed onto the surface of the composite steel core, and a composite steel core welding rod is obtained after drying at 300°C for 150 minutes. In this comparative example, the weight of the powder core is 23% of the total weight of the welding rod, the weight of the steel strip is 36% of the total weight of the welding rod, the weight of the coating is 41% of the total weight of the welding rod, and the amount of binder added is 21% of the total weight of the coating powder.
[0091] Comparative Example 2
[0092] The welding rod in this comparative example includes a welding core and a coating, and the coating is wrapped on the surface of the welding wire. The welding core is a high manganese steel core, including the following components and the weight percentage of each component is: C: 0.35-0.46%, Si: 0.06~0.18%, Mn: 22~30%, Cr: 3.7~4.6%, Ni: 1.8~2.5%, Mo: 1.3~2.1%, S≤0.015%, P≤0.015%, and the balance is Fe and unavoidable impurities. The coating includes the following components and the weight percentage of each component is: 47 parts of marble, 4.2 parts of strontium carbonate, 27 parts of fluorite, 7.5 parts of rutile, 4.5 parts of phlogopite, 3.6 parts of silicon micropowder, 3.1 parts of alumina, 0.6 parts of CMC, and 0.5 parts of potassium alginate.
[0093] The components of the coating are sieved separately and weighed and mixed according to the above ratio to obtain a coating powder, and a water glass binder is added to the coating powder and stirred evenly to obtain a coating mixture. The coating mixture is pressed on the surface of the high manganese steel core, and dried at 340°C for 140 minutes to obtain a high manganese high-strength steel welding rod. In this comparative example, the weight of the welding core is 54% of the total weight of the welding rod, the weight of the coating is 46% of the total weight of the welding rod, and the amount of the binder added is 21% of the total weight of the coating powder.
[0094] Welding tests were carried out on the welding rods prepared in Examples 1 to 6, Comparative Example 1 and Comparative Example 2. The welding process performance is shown in Table 1, and the mechanical properties of the deposited metal of the welding rods are shown in Table 2.
[0095] Table 1: Welding process performance of welding rods prepared in Examples 1 to 6, Comparative Example 1 and Comparative Example 2
[0096]
[0097] Table 2: Mechanical properties of deposited metals of welding rods prepared in Examples 1 to 6, Comparative Example 1 and Comparative Example 2
[0098]
[0099] As shown in Tables 1 and 2, the composite steel core high manganese high-strength steel electrode has good arc stability, small spatter, beautiful shape, easy slag removal, and no tail red problem during welding. Compared with conventional high manganese high-strength steel electrodes, the mechanical properties of the deposited metal are better, and it is suitable for the welding of high manganese high-strength steel.
[0100] The composite steel core high manganese high-strength steel welding rod of the present application has a powder core wrapped inside a steel strip to form a composite steel core, and a coating is wrapped outside the composite steel core. Since the inside of the composite steel core is not solid, even when the temperature rise of the steel core is large during ultra-large current welding, the external expansion of the steel core is much smaller than the internal expansion, and no large pressure is exerted on the external coating. Therefore, there is no problem of coating cracking or falling off, and efficient welding can be achieved to reduce waste. Furthermore, lithium fluoride with excellent arc stabilization performance is added to the powder core as an arc stabilizer. Since the powder core is wrapped in a steel strip, the moisture absorption of lithium fluoride can be effectively alleviated. Therefore, the arc is more stable and the spatter is smaller during welding, which is more conducive to the welder to control the molten pool and obtain high-quality welds. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0101] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A composite steel core high manganese high strength steel welding rod, comprising a powder core, a steel strip and a coating, wherein the powder core is wrapped inside the steel strip, and the coating is coated outside the steel strip, characterized in that: Based on 100 parts by weight of the powder core, the powder core includes the following components and the weight parts of each component are respectively: 50-62 parts of electrolytic manganese powder; 5-10 parts of chromium powder; 5-8 parts of nickel powder; 0.8-1.5 parts of copper powder; 1.5-3 parts of 45# ferrosilicon; 3-6 parts of ferrochromium nitride; 1.5-3 parts of ferroboron; 0.5-1.5 parts of lithium fluoride; 0.8-1.2 parts of graphite; the remainder is reduced iron powder and unavoidable impurities.
2. The composite steel core high manganese high strength steel welding rod according to claim 1, characterized in that: The steel strip is a low-carbon steel strip, and the steel strip includes the following components and the weight percentage of each component is: C≤0.04%, Mn: 0.10%~0.25%, Si≤0.05%, S≤0.02%, P≤0.02%, and the rest is Fe and unavoidable impurities.
3. The composite steel core high manganese high strength steel welding rod according to claim 1, characterized in that: The drug coating comprises the following components, and the weight proportions of the components are respectively: 40-50 parts of marble, 3-6 parts of strontium carbonate, 25-30 parts of fluorite, 6-10 parts of rutile, 3-5 parts of phlogopite, 2-4 parts of silicon micropowder, 2-4 parts of aluminum oxide, 0.1-1 parts of carboxymethyl cellulose, and 0.1-1 parts of potassium alginate.
4. The composite steel core high manganese high strength steel welding rod according to claim 1, characterized in that: The weight of the powder core is 22-27% of the total weight of the welding rod; the weight of the steel strip is 28-38% of the total weight of the welding rod; and the weight of the coating is 40-45% of the total weight of the welding rod.
5. A method for preparing the composite steel core high manganese high strength steel welding rod according to any one of claims 1 to 4, characterized in that: The following steps are involved: The components of the powder core are sieved separately and weighed according to the ratio, and mixed evenly to obtain a powder core mixed powder; Wrapping the powder core mixed powder in a steel strip to obtain a seamless composite steel core; The components of the coating are sieved respectively and weighed and mixed according to a ratio to obtain a coating powder, and a binder is added to the coating powder and stirred evenly to obtain a coating mixture; The coating mixture is press-coated on the surface of the seamless composite steel core, and after drying, a composite steel core high-manganese high-strength steel welding rod is obtained.
6. The preparation method according to claim 5, characterized in that: Electrolytic manganese powder, chromium powder, nickel powder, copper powder, 45# ferrosilicon, ferrochromium nitride, ferroboron, reduced iron powder, lithium fluoride and alumina passed through a 60-mesh sieve; marble, strontium carbonate, fluorite, rutile and phlogopite passed through a 40-mesh sieve; silicon micropowder passed through a 120-mesh sieve.
7. The preparation method according to claim 5, characterized in that: Wrapping the powder core mixed powder in the steel strip to obtain a seamless composite steel core comprises the following steps: Rolling the steel strip into a U-shaped groove; Filling the powder core mixed powder into the U-shaped groove; The U-shaped groove containing the powder core mixed powder is closed, rolled into an O-shape, welded, and drawn to a set diameter.
8. The preparation method according to claim 5, characterized in that: The diameter of the seamless composite steel core is 2.5-5 mm.
9. The preparation method according to claim 5, characterized in that: The added amount of the binder is 19-21% of the total weight of the coating powder, and the binder is a water glass binder with a potassium-sodium weight ratio of 1:
1.
10. The preparation method according to claim 5, characterized in that: The drying temperature is 300~350℃ and the drying time is 120~150min.
